2016
DOI: 10.1002/gps.4517
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to psychotropics in the French older population living with dementia: a nationwide population‐based study

Abstract: This nationwide, population-based, drug-used study showed for the first time that older patients with dementia are chronically overexposed not only to antipsychotics but also to psychotropics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Breining et al . reported that older patients with dementia utilized antipsychotics and antidepressants more frequently than healthy participants did in an age‐matched population. Tosto et al .…”
Section: Discussionmentioning
confidence: 99%
“…Breining et al . reported that older patients with dementia utilized antipsychotics and antidepressants more frequently than healthy participants did in an age‐matched population. Tosto et al .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the adjusted OR for dementia was reduced in patients using tricyclic agents, but use of other classes such as SSRIs and other antidepressants was associated with an increased risk of dementia. A separate prospective, nationwide, population-based cohort study in France78 suggests exposure to psychotropics was higher in patients with dementia, but neither of these two population-based studies actually prove causality.…”
Section: Current Approaches To Manage Visceral Pain In Patients With Ibsmentioning
confidence: 96%
“…A percentage of antidepressants in this population might have been prescribed for neuropathic pain. A high rate of use of antidepressants has been described also in other European countries [51][52][53][54][55]. This aspect has a fundamental importance because, despite the potential of antidepressants for neurogenesis [56,57], the use of drugs endowed with anticholinergic burden can worsen cognitive decline, increase the risk of falls, institutionalization, and mortality [58][59][60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%